Nyelvpolitika: harc a hatalomért (az ukrán államnyelvi törvény apropóján) - Beregszászi Anikó; Csernicskó István; Берегсасі Аніко; Черничко Степан; Aniko Beregszaszi; Csernicsko Istvan (Magyar Nyelvtudományi Társaság, 2020)
Az alábbiakban a 2019. április 25-én elfogadott ukrán államnyelvi törvény példáján mutatjuk be, hogy a látszólag az ukrán nyelv védelmében, illetve a társadalom egy része nyelvi gyakorlatának megváltoztatása érdekében hozott törvény révén a nyelvpolitika hogyan szolgálhat eszközként a hatalom megszerzéséért folytatott harcban és a társadalmi egyenlőtlenségek kialakításában és újratermelésében.

Abstract. One of the main goals of language policy is considered to be the avoidance or management of language conflicts. In reality, however, language policy is an effective tool for achieving the unequal distribution of social goods and political capital. The Law of Ukraine “On Supporting the Functioning of the Ukrainian Language as the State Language” was adopted on April 25, 2019. In this article we show how language policy can serve as a tool in the struggle for power and in the formation and reproduction of social inequalities through the law seemingly born to protect the Ukrainian language. In the article, we also show that in power struggles, language policy often does not serve to avoid conflicts over language, but on the contrary: it causes internal and external conflicts.
Language policy: struggle for power (through the prism of the Ukrainian state language law)
Keywords: nyelvpolitika; államnyelv; nyelvtörvény; kisebbségi jogok; nyelv és hatalom; egyenlőtlenség; Ukrajna